Spectrum-Efficient Multitarget Vital Sign Monitoring Using Metamaterial-Integrated Space-Time-Coding Transmitting Array - Li, Shuping; Gao, Donglin; Vosoughitabar, Shaghayegh; Wu, Chung-Tse Michael (IEEE microwave and wireless technology letters (Print), 2024)
A metamaterial-integrated space-time-coding (STC) transmitting array incorporating direct antenna modulation (DAM) is proposed in this work to detect the multitarget vital sign signals, including respiration and heart rates. A series metamaterial (MTM) zeroth-order power divider is used to uniformly distribute the carrier signal to each element of the array. DAM, applied to each antenna element, creates a 180° phase shift in the far-field while keeping the amplitude uniform, which is controlled via a programmed FPGA. By feeding specific time-modulated sequences to each antenna element, the radiation patterns of the resulting harmonic frequencies can be accurately directed toward different locations. Moreover, the modulation frequency is much less than the carrier frequency. This leads harmonic beam steering, to occupy a much narrower spectrum compared with frequency-dependent leaky wave antennas (LWAs), thereby enhancing spectral efficiency. The effectiveness of this MTM-integrated STC transmitting array in multitarget sensing is demonstrated through experimental tests involving various actuators and human subjects.